Research on leakage characteristics of working clearances of hydrogen circulation pump - Zhai, Huanle; Li, Wei; Chu, Xiaomeng; Mu, Honggang; Shen, Chungen (Frontiers in Energy Research, 2024)
The volumetric efficiency of the hydrogen circulation pump (HCP) is mainly affected by the amount of leakage in working clearances. Studying the leakage characteristics of working clearances is of great significance for optimizing the performance of the HCP. Therefore, this paper developed a three-blade elliptical conjugate rotor HCP, and compared the results of experiments and simulations for different working conditions.On this basis, the flow rate, pressure, and internal flow field changes of radial clearance models and axial clearance models with four different scales of 0.1mm, 0.14mm, 0.18mm, and 0.22mm were studied. The results indicate that: under four different pressure ratios and rotational speeds, the simulation results using the overlapping grid method showed a maximum errordifference of 4.17% compared to the experimental results, verifying the reliability of the simulation calculation method; the average flow rate of the HCP is linearly inversely proportional to both the radial clearance and the axial clearance, with a decrease rate of 11.6Nm 3 /h and 5.8Nm 3 /h as the clearance size increases by 0.04mm; the radial clearance leakage of the same size is higher than the axial clearance, the leakage value in the radial clearance between the rotors is higher than that between the rotor and the pump casing, and the internal leakage of axial clearance is not evenly distributed, with higher leakage value in the middle area than that in the left and right areas.